2015
DOI: 10.1111/ddi.12363
|View full text |Cite
|
Sign up to set email alerts
|

Host promiscuity in symbiont associations can influence exotic legume establishment and colonization of novel ranges

Abstract: Aim Invasive Acacia species have negatively impacted natural areas in multiple regions around the globe. Almost 400 Acacia species have been introduced outside their native ranges in Australia; approximately 6% have become invasive, 12% are naturalized, and 82% have no record of naturalization or invasion. This variation in invasiveness provides a comparative framework in which to examine mechanisms that either promote or constrain establishment and colonization of species in novel regions. Here, we experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 48 publications
2
65
0
1
Order By: Relevance
“…Inadequate population density of compatible rhizobia or appropriate environmental conditions for effective nitrogen fixation in introduced ranges are viable explanations for our results. This explanation would suggest that symbiotic legume hosts and their compatible symbionts would frequently need to be introduced simultaneously or that introductions would favour legumes that are able to form associations with a broad diversity of rhizobia1718, which is consistent with empirical findings from previous studies examining introduced Acacia species181920.…”
Section: Discussionsupporting
confidence: 86%
“…Inadequate population density of compatible rhizobia or appropriate environmental conditions for effective nitrogen fixation in introduced ranges are viable explanations for our results. This explanation would suggest that symbiotic legume hosts and their compatible symbionts would frequently need to be introduced simultaneously or that introductions would favour legumes that are able to form associations with a broad diversity of rhizobia1718, which is consistent with empirical findings from previous studies examining introduced Acacia species181920.…”
Section: Discussionsupporting
confidence: 86%
“…Bradyrhizobium species are the predominant N 2 -fixing rhizobia associated with acacias (e.g., refs 47 and 48). N 2 -fixing symbionts enhance growth and competitive ability of their host plants 49 , which consequently influences plant invasiveness 50 . Interestingly, it has been reported that seven of nine selected acacia species grew better in association with Bradyrhizobium phylotypes than with members of the genera Burkholderia , Rhizobium and Ensifer 51 .
Figure 5Relative frequency versus relative abundance of biomarker taxa, coloured according to phylum, for bulk and rhizosphere soils (logarithmic LDA score ≥2, P < 0.05).
…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, introduced plants can form ‘novel associations’ with native symbionts or co-xenic novel associations (Nuñez and Dickie 2014) can be formed between symbionts from different regions (Klock et al 2015; Le Roux et al 2016). The level of interaction specificity, coupled with chances of co-introduction, may therefore have serious fitness consequences for introduced plants.…”
Section: Evolutionary Mechanisms Underlying Tree Invasionsmentioning
confidence: 99%